Ultrasound Deep Brain Stimulation Modulates Body Temperature in Mice - Na Pang; Wen Meng; Yongsheng Zhong; Xiufang Liu; Zhengrong Lin; Tianxu Guo; Hui Zhou; Lin Qi; Long Meng; Lisheng Xu; Lili Niu (IEEE, 2022)
Body temperature plays a critical role in rehabilitation, and numerous studies proved that the regulation of body temperature contributes to the sensorimotor recovery of patients with brain diseases such as stroke. The hypothalamus plays a key role in thermoregulation. Ultrasound deep brain stimulation (UDBS) can noninvasively modulate deep brain nuclei and have potential applications in the treatment of Parkinson’s disease, Alzheimer’s disease, and depression, among others. The purpose of this study was to investigate whether ultrasound stimulation of the hypothalamus could regulate body temperature in free-moving mice. Results showed that thermoregulation was related to ultrasonic parameters (pulse repetition frequency (PRF), duty cycle, total time, and acoustic pressure). UDBS of the preoptic area of the anterior hypothalamus at 500 Hz PRF could significantly reduce body temperature ( $\text{T}\,\,= -0.25\,\,± \,\,0.073\,\,^{° }\text{C}$ at t = 5 min, $\text{T}\,\,= -0.51\,\,± \,\,0.19\,\,^{° }\text{C}$ at t = 10 min, $\text{T}\,\,= -0.84\,\,± \,\,0.27\,\,^{° }\text{C}$ at t = 15 min). Meanwhile, UDBS of the dorsomedial hypothalamus at 10 Hz PRF triggered a significant increase in body temperature ( $\text{T}\,\,=0.5\,\,± \,\,0.077\,\,^{° }\text{C}$ at t = 5 min, $\text{T}\,\,=1.16\,\,± \,\,0.23\,\,^{° }\text{C}$ at t = 10 min). These results suggest that UDBS, as a noninvasive neuromodulation tool, may play a key role in the future clinical treatment of malignant hyperthermia and hypothermia.